Pendidikan Karakter Dalam Makna Pantang Larang Di Desa Pangkalan Buton Dan Rantau Panjang Kecamatan Sukadana Kayong Utara - Utut Sugiatno, Septian (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This study aims to reveal character education in the meaning of pantang larang [taboo] in Pangkalan Buton and Rantau Panjang Villages, Sukadana Sub-District, Kayong Utara Regency. The method used in this research is descriptive qualitative. In this case it describes the object under study and explains the data thoroughly and systematically. Then after the data is considered to be sufficient, the next stage is data analysis and continued with conclusion drawing. Pantang larang that is still in practice today in Pangkalan Buton and Rantau Panjang is a belief for some people as a norm and adab [good manners] to balance technological advancement in today's digital era, and therefore it indirectly becomes the 'police' in the midst of the growing modernization. Pantang larang that develops in the Pangkalan Buton and Rantau Panjang Village Communities has relevance to character education, especially with regard to religious attitudes and values, resilience, and caring.